Electromyographic analysis of deep trunk muscles during sports activities - Okubo, Y. (Sports injuries and prevention, 2015)
An understanding of the function of trunk muscles is important for the treatment of low back pain as well as for the improvement of athletic performance. In particular, the importance of deep trunk muscles (local muscles) has been documented in the recent literature. In this chapter we report on investigation about activity patterns of deep trunk muscles during lumbar stabilization exercises and sports activities. We recorded muscle activity using intramuscular electrodes. The results provide information that allows us to propose effective exercises for enhancing deep trunk muscle activity and improve the complex coordination of trunk muscle activity that is important during sports.